Boron Nitride based Ternary Nanocomposites with Different Carbonaceous Materials Decorated by Polyaniline for Supercapacitor Application. Issue 13 (2nd April 2019) - Maity, Chandan Kumar; Hatui, Goutam; Sahoo, Sumanta; Saren, Pupulata; Nayak, Ganesh Chandra
Abstract: In this article, we have emphasized on the utilization of hexagonal BN (a 2D material) for supercapacitor application in combination with various carbonaceous materials (GO, RGO, CNT) and polyaniline (PANI). The formation of composite as well as interaction between the individual components in the ternary composites was confirmed by UV, FTIR, and XRD analysis. The morphological analysis established the uniform deposition of polyaniline nanofibers on the exfoliated BN and carbonaceous materials. Among the ternary nanohybrids, BN/CNT/PANI composite exhibited highest specific capacitance of 387.5 Fg −1 at a current density of 1 Ag −1 in 1 M KCl. The ternary composite also achieved a high energy density of 34.44 Whkg −1 at a power density of 400 Wkg −1 . Further, the ternary nanohybrid BN/CNT/PANI retained 87% of specific capacitance after 6000 charging disharging cycles. All these superior electrochemical properties demonstrates potentiality of BN/CNT/PANI for supercapacitors. Abstract : Boron Nitride based Ternary Nanocomposites with Different Carbonaceous Materials Decorated by Polyaniline for Supercapacitor Application. Ternary supercapacitor electrodes based on hexagonal BN, carbonaceous materials, and polyaniline are developed.